The Effect of Annealing Treatment on n-Cu2O Thin Film Fabrication - Mohd ismail, Anis zafirah; Mohamad, Fariza; Muhd Nor, Nik Hisyamudin; Izaki, Masanobu (International Journal of Integrated Engineering, 2020)
This experiment is about fabrication of homojunction n-type cuprous oxide (Cu2O) thin film by using electrodeposition method. The Cu2O thin films were deposited on fluorine doped tin oxide (FTO) substrates by using copper acetate based solution through potentiostatic electrodeposition method. The n-type Cu2O was fabricated at pH 6.3 with a fixed potential of -0.125V vs. Ag/AgCl and time deposition of 30 minutes. Annealing treatment was introduced to enhance the properties of the thin films.  The quality of Cu2O thin films were studied in varied the annealing duration. Morphological, structural, optical and electrical properties were characterized using X-Ray Diffractometer, Field Emission-Scanning Electron Microscopy, Ultraviolet-visible Spectroscopy and Four Point Probe, respectively.